27 Decision-Making Capacity Assessment: Occupational Therapy's Contribution within a Multidisciplinary Approach. (16th September 2019) - Usher, Ruth; Stapleton, Tadhg
Abstract: Background: Increasing age and life expectancy, alongside the growing incidence of chronic conditions and dementia-related diseases, indicate more older individuals are likely to experience challenges regarding decision-making capacity. In Ireland, the Assisted Decision Making (Capacity) Act 2015 provides a statuary framework for adults who are experiencing difficulties with decision-making. This legislation has significant implications for all who work in health and social care, especially those working with older adults. An online survey was conducted to explore occupational therapy practices regarding decision-making capacity assessment and factors impacting on engagement in this area. Methods: Occupational therapists in Ireland were invited to participate in a cross-sectional online questionnaire. Results: One hundred and seventy-two occupational therapists responded. Most occupational therapists (65.77%, n=98) reported involvement in decision-making capacity assessments, particularly those working with older adults. Occupational therapists were more frequently requested to contribute to assessments of capacity regarding independent living (79.19%, n=118), driving (45.89%, n=67), and financial management (44.44%, n=64). Occupational therapists reported using a combination of approaches to inform decision-making capacity assessment, including interviews, observations and assessments of cognition and functional performance, and emphasised a strength-based approach. Many participants reported decision-making capacity assessment is more difficult than other aspects of practice and that they are not satisfied with decision-making capacity assessment procedures in their workplace. A large majority (91.86%, n=113) reported occupational therapists would benefit from additional training and practice resources for decision-making capacity assessment. Conclusion: The study confirms that occupational therapists have a role to play in assessment of decision-making capacity assessment, particularly regarding independent living. However, the recommended approach to assessment should include all appropriate multidisciplinary team members. There is need for further education, resources and guidelines for occupational therapists and other healthcare professionals to better guide decision-making capacity assessment.